Upaya Meningkatkan Pengetahuan Masyarakat tentang Kesehatan dan Memberikan Ide-Ide Usaha Tanpa Modal Untuk Ibu Rumah Tangga serta Pemanfaatan Kecerdasan Buatan Untuk Pemasaran di RW 05 Kelurahan Babakan Asih Kecamatan Bojongloa Kaler Kota Bandung - Ekawati, Dian; Tambunan, Roselina; Angelina, Ria; Hotmaida, Linda; Sariningsih, OD; Rejeki, Sri; Adi Bangun Wiratmo, Yohanes (PADMA, 2024)
Community Service Activities (Pengmas) carried out by Working Group (POKJA) 5 of the Immanuel Bandung Health Institute in RW 05 Sub District Babakan Asih, Bandung City. Community service aims to increase public knowledge about health and providing business ideas without capital for housewives and using artificial intelligence for marketing in Sub District Babakan Asih, Bandung City. The activity involved 7 lecturers from the Professional Nursing Program, Bachelor of Public Health, Diploma 3 in Nursing, Diploma 3 in Midwifery and Diploma 3 in Hospital Service Management (MPRS). The community service method is carried out by means of counseling and question and answer. The media used are laptops, LCD, LCD screens and speakers to display material in the form of power points and interactive videos. The material presented to the public was carried out in just 1 stage and took place in the courtyard of RW 05 Office. The community service was held on Wednesday 13th November 2024, the material presented included: Degenerative Diseases, Prevention of Tuberculosis, Use of Contraceptives, How to Know the Fertile Period for Those Who Are Using Natural Birth Control and Providing Business Ideas Without Capital For Housewives and Using Artificial Intelligence For Marketing, as well as collecting data through Pre and Post Tests regarding Hypertension. The recommendation that can be recommended is that monitoring can be carried out in the area regarding what counseling materials have been provided, whether there are changes in attitudes and behavior or not.